The Role of Kallikrein 7 in Tumorigenesis - Xiang, Fengyi; Wang, Yueqing; Cao, Chunyu; Li, Qingyun; Deng, Hao; Zheng, Jun; Liu, Xiaowen; Tan, Xiao (Current Medicinal Chemistry, 2022)
Kallikrein 7 (KLK7) is a secreted serine protease with chymotrypsic protease activity. Abnormally high expression of KLK7 is closely related to the occurrence and development of various types of cancer. Therefore, KLK7 has been identified as a potential target for cancer drug development design in recent years. KLK7 mediates various biological and pathological processes in tumorigenesis, including cell proliferation, migration, invasion, angiogenesis, and cell metabolism, by hydrolyzing a series of substrates such as membrane proteins, extracellular matrix proteins, and cytokines. This review mainly introduces the downstream cell signaling pathways involved in the activation of KLK7 and its substrate-related proteins. This review will not only help us to better understand the mechanisms of KLK7 in regulating biological and pathological processes of cancer cells but also lay a solid foundation for the design of inhibitors targeting KLK7.
Keywords: cancer treatment